Characteristics of suspended sediment concentration and distribution of maximum coastal turbidity of the Mekong river - Nguyen, Ngoc Tien (Vietnam Journal of Marine Science and Technology, 2023)
This paper presents the results of applying a 3D mathematical model to study the in the Mekong riverside area’s maximum turbidity zone (MTZ). This study has established and calibrated a three-dimensional system model with a combination of hydraulics-waves and suspended sediment transport with measured data in the study area. Based on the calculated scenarios for the flood and the dry seasons, the results show the occurrence of MTZs in the riparian zone of the Mekong river with typical suspended sediment concentrations ranging from 0.04–1.0 kg/m3 dry season and 0.2–1.1 kg/m3 flood season. The location and size of the MTZs change seasonally with the interaction between freshwater and tidal oscillations. They appear more in the dry season. At high tide, seawater with high salinity intrudes into estuaries with a range of up to 50 km, causing disturbance and flocculation. While in the flood season, the distribution of the largest turbidity has moved the floodplain with a range of about 20 km.